Pengaruh Edukasi terhadap Pengetahuan Hipertensi Masyarakat di Kabupaten Kuantan Singingi, Riau - Kodriati, Nurul; Ngupulu, Ulfa Afrianti (DHARMA BAKTI, 2023)
Hypertension is no longer just a health issue in Indonesia; it has become a global issue. Globally, hypertension has risen to 74,5 million people. According to Riskesdas 2013, the national prevalence of hypertension is 25.8%, with only one-third of those diagnosed having hypertension and 0.7% having a higher risk of developing hypertension. The purpose of this research is to educate people about hypertension and how to prevent it. The method used in this study is community diagnostic, in which participants conduct a lengthy survey to learn about the primary health issues that are occurring in the study area. Paired T-test was used to compare respondents’ knowledge pre and post intervention. A survey conducted in Desa Sungai Sirih RT 20 RW 07 Kuantan Singingi found that people's desire to live a healthy life has a significant impact on the level of hypertension in the area. Following that, priority health issues and interventions will be prioritized. The use of posters in hypertension education is recommended in order to increase public awareness. The knowledge of the respondents after the intervention was significantly increased compared before intervention. Education about hypertension should continue in order to improve the prevalence and effectiveness of hypertension treatment.